Upaya Peningkatan Eksistensi Sekolah dengan Pembenahan Tugu SMA Negeri Matakali - Sukmawati Said; Dirga Kaso Sanusi; Riskawati Riskawati; Ria Rezki Hamzah; R. R. A. Putra (Program Studi Pendidikan IPA Fakultas MIPA Universitas Negeri Makassar, 2024)
School is an institution to provide education to students. There is an appointed time and space for teaching and learning. According to the 2013 National Education System Law, Article 3 states that the entire educational process must be aimed at developing the overall human potential in order to achieve a prosperous life, both physically, mentally and spiritually. The purpose of education itself is in line with the ideals of the Indonesian state which wants a dignified nation's civilization, developing a complete human being by ensuring adequate facilities and infrastructure to support this goal. SMAN Matakali is one of the schools that supports programs to restore facilities and infrastructure, namely by empowerment and restoration of school monuments, this was initiated by various factors, one of which was the lack of existence. Therefore, through this activity, we hope to foster the spirit of sharing school elements to restore the school monument as one of the icons of SMAN Matakali. The method of this service activity uses descriptive qualitative research methods. The subjects in this service activity are all elements of SMAN Matakali. Based on the research results, it is known that all elements of SMAN Matakali are directly involved in the process of planning, procurement, maintenance and supervision of recovery activities. The results of this service activity show the level of success with the responsibility or action taken by all elements of SMAN Matakali.